2014
DOI: 10.2478/fco-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of relatively new chemotherapeutic agents on the outcome of Egyptian patients with advanced malignant pleural mesothelioma

Abstract: Purpose: Patients with malignant pleural mesothelioma (MPM) are well known to have poor response to chemotherapy. The aim of this work was to evaluate the efficacy and safety of new chemotherapeutic agents for the treatment of Egyptian MPM patients. Patients and methods: The first study was a non-randomised, open-label trial. It included 34 eligible patients who were assigned to receive either cisplatin–pemetrexed or pemetrexed alone if cisplatin was contraindicated for a maximum of eight cycles. In the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These cancer types include malignant mesothelioma, head and neck cancer, liver cancer, cervical cancer, and stomach cancer. [12][13][14][15][16][17] Sun et al carried out a prospective study and found that raltitrexed increases radiation sensitivity of ESCC. 18 However, the effect of irinotecan combined with raltitrexed in ESCC still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cancer types include malignant mesothelioma, head and neck cancer, liver cancer, cervical cancer, and stomach cancer. [12][13][14][15][16][17] Sun et al carried out a prospective study and found that raltitrexed increases radiation sensitivity of ESCC. 18 However, the effect of irinotecan combined with raltitrexed in ESCC still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, raltitrexed was found to exhibit antitumor properties in various cancer types through its direct antiproliferation and induction of apoptosis effects in preclinical studies. These cancer types include malignant mesothelioma, head and neck cancer, liver cancer, cervical cancer, and stomach cancer 12–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation